2010
DOI: 10.1016/j.labeco.2009.05.007
|View full text |Cite
|
Sign up to set email alerts
|

Boon or bane? Others' unemployment, well-being and job insecurity

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

33
220
3
5

Year Published

2011
2011
2022
2022

Publication Types

Select...
6
2
1

Relationship

0
9

Authors

Journals

citations
Cited by 325 publications
(261 citation statements)
references
References 42 publications
33
220
3
5
Order By: Relevance
“…However subjective assessments of job insecurity also come with their own complications, such as capturing non-pecuniary benefits (Young, 2010) and are plausibly endogenously affected by health (and in particular mental health) either due to greater feelings of general anxiety, or a compromised ability to accurately predict future outcomes. 3 Nonetheless these indices have been successfully used in studies of health and wellbeing, notably by Green (2011) and Otterbach and Sousa-Poza (2014) who examined how employability mediates the mental health effects of A c c e p t e d M a n u s c r i p t job insecurity, and by Clark et al (2010) who assessed its modifying effect on the relationship between unemployment and wellbeing.…”
Section: Datamentioning
confidence: 99%
“…However subjective assessments of job insecurity also come with their own complications, such as capturing non-pecuniary benefits (Young, 2010) and are plausibly endogenously affected by health (and in particular mental health) either due to greater feelings of general anxiety, or a compromised ability to accurately predict future outcomes. 3 Nonetheless these indices have been successfully used in studies of health and wellbeing, notably by Green (2011) and Otterbach and Sousa-Poza (2014) who examined how employability mediates the mental health effects of A c c e p t e d M a n u s c r i p t job insecurity, and by Clark et al (2010) who assessed its modifying effect on the relationship between unemployment and wellbeing.…”
Section: Datamentioning
confidence: 99%
“…Mayraz et al (2009) found income comparisons to be a much better predictor of subjective well-being for men than women. Using econometric techniques on national panel datasets, Clark (2003), Clark et al (2010) and Shields et al (2009) all found that the subjective well-being of unemployed men rises when faced with other people's unemployment at the regional level. None found any effect for women, apart from Clark (2003) who found a weak relationship.…”
Section: Pathway 2: Statusmentioning
confidence: 99%
“…On the societal level, the economic price of unemployment includes collective burden of benefits for the unemployed, other social welfare expenditures and lower tax revenues (Bjarnason & Sigurdardotirr, 2003). In addition, unemployment is considered to be the most important cause of poverty, frequently related with other social problems, such as outrage or rightwing extremism (Krueger & Pishke, 1997) and lower quality of life for all members of a society (Clarck, Knabe, & Ratzel, 2010). On the individual level, unemployment leads to decline in well-being.…”
Section: Introductionmentioning
confidence: 99%